Protect data and be alert to online cyber threats - Irman, Khalil; Mimi Rabita, Abdul Wahit (2021)
PEKAN, 18 May 2021 - Universiti Malaysia Pahang (UMP), through the Centre for Information and Communication Technology (PTMK), advises university residents to always ensure that all internet-related applications are updated and upgraded and always be careful with emails and links from suspicious sources.